Assessing the Social Determinants of Health and Adverse Childhood Experiences in Patients Attending a Children's Hospital Cleft Palate-Craniofacial Program. (December 2022) - Ponton, Ethan; Courtemanche, Rebecca; Singh, Tanjot K.; Duffy, Damian; Courtemanche, Douglas J.; Loock, Christine
Objective : This study aimed to describe the social determinants of health (SDoH) for patients receiving multidisciplinary team care in a Cleft Palate-Craniofacial program, develop responsive and consistent processes to include trauma-informed psychosocial histories, promote discussions about additional "non-medical" factors influencing health and surgical outcomes, and demonstrate that these activities are feasible in the context of multidisciplinary patient-provider interactions. Design : Single-site, cross-sectional study using a questionnaire. Setting : Participants were recruited from a provincial quaternary care Cleft Palate-Craniofacial program at British Columbia Children's Hospital in Vancouver, BC, Canada. Participants : 290 families completed the questionnaire. Results : 34% of families experience significant barriers to accessing primary health care, 51% struggle financially, and 11% scored four or more on the Adverse Childhood Experiences scale. Furthermore, 47% reported not having adequate social support in their lives, and 5% reported not feeling resilient at the time of the survey. Conclusion : Patients with cleft and craniofacial anomalies have complex needs that extend beyond the surgical and medical care they receive. It is critical that all Cleft and Craniofacial teams incorporate social histories into their clinic workflow and be responsive to these additional needs. Discussions surrounding SDoH and adversity are welcomed by families; being involved in the care and decision-making plans is highly valued. Healthcare providers can and should ask about SDoH and advocate for universal access to responsive, site-based, social work support for their patients.